Relationship of Tumor Thickness with Neck Node Metastasis in Buccal Squamous Cell Carcinoma: An Experience at a Tertiary Care Hospital - Ahmed,Sadaf Qadeer (2017)
Abstract Introduction Squamous cell carcinoma is the most common malignancy of the head and neck, with the buccal mucosa being the most common site involved. Early locoregional metastasis is a hallmark of this disease, and early stage tumors may harbor metastatic nodes that are occult. Certain parameters can help identify high-risk patients for whom the pattern of occult nodal metastasis can be predicted. Tumor thickness is one such objective parameter. Objective To determine the relationship of tumor thickness with neck node metastasis in squamous cell carcinoma of the buccal mucosa. Methods A retrospective chart review of 102 patients with biopsy-proven squamous cell carcinoma of the buccal mucosa with N0 Necks was performed. All patients underwent tumor resection with neck dissection, and the tumor thickness was measured. Univariate and multivariate analyses were performed. Results A total of 102 patients, of which 73.53% were males and 26.47% were females. Themean age of the patients was 49.3 ± 11.1 years. It was found that the risk of neck node metastasis in buccal squamous cell carcinoma increases 35.5 times for a tumor thickness ≥ 2 mm, and the risk of neck nodemetastasis in buccal squamous cell carcinoma decreases by 0.58 times for each centimeter decrease in tumor size, while the rate of occult neck lymph node metastasis was found to be 37%. Conclusion We conclude that tumor thickness is significantly related with neck nodal metastasis in buccal squamous cell carcinoma, considering the age of the patient and the size of the tumor.